2015
DOI: 10.1111/jfr3.12156
|View full text |Cite
|
Sign up to set email alerts
|

Local perception of floods in the Czech Republic and recent changes in state flood management strategies

Abstract: A shift from flood protection to flood risk management is occurring in many Western countries, but less is known about the social perception of floods and flood management changes in Central and Eastern Europe. The objective of this paper is to study the social perception of selected water‐related issues and to find possible compatibilities with existing flood management. A sociological survey was conducted within a local population living in flood plains in South Bohemia (N = 89). The results are discussed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 57 publications
(119 reference statements)
1
29
0
Order By: Relevance
“…These authors note that the cost of government support for all properties in flood risk areas would be excessive, but they considered subsiding flood protection for the poorest and oldest householders a moral imperative. In their survey of 86 people living in flood affected areas in South Bohemia (Czech Republic), Vávra et al [40] found that 74% of the respondents believe that subsidies should be provided to farmers who increase retention of rainwater on their land.…”
Section: Opinions Of House-hold Level Flood Protection Measuresmentioning
confidence: 99%
“…These authors note that the cost of government support for all properties in flood risk areas would be excessive, but they considered subsiding flood protection for the poorest and oldest householders a moral imperative. In their survey of 86 people living in flood affected areas in South Bohemia (Czech Republic), Vávra et al [40] found that 74% of the respondents believe that subsidies should be provided to farmers who increase retention of rainwater on their land.…”
Section: Opinions Of House-hold Level Flood Protection Measuresmentioning
confidence: 99%
“…Although the floods were not as severe in Prague as in other municipalities, the volume of destruction was greatest in the capital, as the waters damaged, inter alia, subway stations and threatened bridges, historical sights, the Prague Zoo, private houses, and sports venues. Damage to property in Bohemia was estimated at more than USD 0.5 billion (Vávra et al, ).…”
Section: Actual Deployment Of the Crisis Mapmentioning
confidence: 99%
“…Several European floods were eminent, for example 2004 and 2005 floods in England (Archer and Fowler, 2015), in summer 2007 (Posthumus et al, 2009;Ochoa-Rodríguez et al, 2015), South West England in spring 2012 (Morris and Brewin, 2013), Southeast France in 2015, Italy in 2015, and last but not least England (Lancashire, Yorkshire, and Greater Manchester) in 2016. European floods in 2013 and Central European floods events in 1997, 2002(Socher and Böhme-Korn, 2008Vávra et al, 2015). The Czech Republic experienced numerous knowledgeable floods in 1997, 1998, 2002, 2006(Vávra et al, 2015Duží et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…European floods in 2013 and Central European floods events in 1997, 2002(Socher and Böhme-Korn, 2008Vávra et al, 2015). The Czech Republic experienced numerous knowledgeable floods in 1997, 1998, 2002, 2006(Vávra et al, 2015Duží et al, 2017). Extreme flood events can affect naturally occurring fish species in rivers (Horwitz, 1978;Poff and Allan, 1995;Gordon et al, 2004), as well as overall fish stocks and cause considerable losses of fish populations in ponds.…”
Section: Introductionmentioning
confidence: 99%